Pengaruh Current Ratio, Return On Equity, dan Net Profit Margin terhadap Return Saham pada Subsektor Telekomunikasi Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Jenny Ramadhanti (Universitas Batanghari Jambi, 2021)
The aim of this research is to provide evidence regarding the effect of solvency ratios and profitability ratios on stock return. The financial ratios studied were Current Ratio, Return on Equity, and Net Profit Margin as independent variables and Stock Return as the dependent variable. The number of samples used in this study were telecommunication companies listed on the IDX which were actively traded from 2016 to 2020. The sampling method used was purposive sampling where sampling was carried out based on certain conditions. The statistical method used in this research is multiple regression method.The results of this study indicate that the variable Current Ratio ,Return on Equity, and Net Profit Margin simultaneously have a significant effect on the stock return, and Return on Equity ratio has a partially effect on Stock Retun.